1996
DOI: 10.1128/iai.64.10.4220-4225.1996
|View full text |Cite
|
Sign up to set email alerts
|

In vitro complement-dependent binding and in vivo kinetics of pneumococcal polysaccharide TI-2 antigens in the rat spleen marginal zone and follicle

Abstract: For a better understanding of the spleen-dependent induction of the humoral immune response against thymus-independent type 2 antigens, we have studied the in vitro and in vivo localization of different capsular pneumococcal polysaccharides (PPSs) in the rat spleen. In this study, we found that in vitro binding of PPS types 3, 4, 6B, 9N/V, 14, and 23F was dependent on complement (probably a C3 fragment) and that the localization was predominantly restricted to the marginal-zone B lymphocytes and the follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 20 publications
5
22
0
3
Order By: Relevance
“…Five days after injections it can be traced in the germinal centres showing a typical FDC associated staining pattern ( Fig. 3) [11]. Rats treated with CP or MTX 2 days before vaccination with PPS showed a same localization pattern as observed in control rats (Table 1).…”
Section: Immunohistochemistrysupporting
confidence: 54%
See 2 more Smart Citations
“…Five days after injections it can be traced in the germinal centres showing a typical FDC associated staining pattern ( Fig. 3) [11]. Rats treated with CP or MTX 2 days before vaccination with PPS showed a same localization pattern as observed in control rats (Table 1).…”
Section: Immunohistochemistrysupporting
confidence: 54%
“…Previously, we have demonstrated that polysaccharides rapidly localize specifically on the splenic marginal zone B cells and not the marginal zone macrophages by immunohistological (double staining) examination of spleens of rats injected with polysaccharides [11]. Within 24 h, PPS shifts to the follicles and at 5 days after vaccination the polysaccharides can be traced in the secondary follicles bound in a FDC like fashion [11]. When injecting polysaccharides 2 days after chemotherapy, we still found localization of polysaccharides within 15 min in the marginal zone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A functional spleen is essential for the immune response to TI-2 antigens [3,10,13]. Absence or dysfunction of the spleen results in an increased risk of infections caused by bacteria that have a polysaccharide capsule [17][18][19].…”
Section: The Importance Of a Functional Spleenmentioning
confidence: 99%
“…The second function of the S-MZ is a more unique one and involves the initiation of an immune response to T cell indepen-dent type 2 (TI-2) antigens [3][4][5][10][11][12]. Based on immunogenicity in congenitally athymic ( nu/nu ) mice and mice with and X-linked immune B cell defect ( xid-mice), antigens are divided in T-cell dependent (TD), T-cell independent type 1 (TI-1) and T-cell independent type 2 (TI-2) antigens.…”
Section: Introductionmentioning
confidence: 99%